Achieving the maqasid of Islamic finance through Social Impact Bonds (SIB) and Sustainable and Responsible Investment (SRI) sukuk - Syed Azman, Syed Marwan Mujahid; Haneef, Mohamed Aslam; Engku Ali, Engku Rabiah Adawiah; Ismail, Suhaiza (UNIDA Gontor Press, 2019)
This paper looks into the underlying principles of Social Impact Bond (SIB) and Sustainable and Responsible Investment (SRI) sukuk as compared to the values embodied within maqasid al-Shari‘ah and maslahah. Through a critical review of literature related to SIB, SRI sukuk, maqasid al-Shari'ah and maslahah, the paper attempts to delineate the elements embedded within these financial tools from an Islamic perspective. The paper explicates that SIB and SRI sukuk are financial mechanisms that epitomises the ethical and moral framework of the Shari‘ah as their underlying principles are congruent with the concepts within maqasid al-Shari'ah and maslahah. Thus, the SIB and SRI sukuk models should be given more attention by Islamic banks and Islamic financial institutions whose philosophical foundation is built upon the principles of maqasid al-Shari'ah and maslahah.